Mesoporous Single‐Crystal Lithium Titanate Enabling Fast‐Charging Li‐Ion Batteries. Issue 18 (25th March 2022) - Jin, Xu; Han, Yehu; Zhang, Zhengfeng; Chen, Yawei; Li, Jianming; Yang, Tingting; Wang, Xiaoqi; Li, Wanxia; Han, Xiao; Wang, Zelin; Liu, Xiaodan; Jiao, Hang; et al.
Abstract: There remain significant challenges in developing fast‐charging materials for lithium‐ion batteries (LIBs) due to sluggish ion diffusion kinetics and unfavorable electrolyte mass transportation in battery electrodes. In this work, a mesoporous single‐crystalline lithium titanate (MSC‐LTO) microrod that can realize exceptional fast charge/discharge performance and excellent long‐term stability in LIBs is reported. The MSC‐LTO microrods are featured with a single‐crystalline structure and interconnected pores inside the entire single‐crystalline body. These features not only shorten the lithium‐ion diffusion distance but also allow for the penetration of electrolytes into the single‐crystalline interior during battery cycling. Hence, the MSC‐LTO microrods exhibit unprecedentedly high rate capability, achieving a specific discharge capacity of ≈174 mAh g −1 at 10 C, which is very close to its theoretical capacity, and ≈169 mAh g −1 at 50 C. More importantly, the porous single‐crystalline microrods greatly mitigate the structure degradation during a long‐term cycling test, offering ≈92% of the initial capacity after 10 000 cycles at 20 C. This work presents a novel strategy to engineer porous single‐crystalline materials and paves a new venue for developing fast‐charging materials for LIBs. Abstract : Mesoporous single‐crystal architecture is performed on the spinel Li4 Ti5 O12 (LTO) anode for ultrafast‐charging lithium‐ion batteries. The unique interconnected porous structure of LTO microrods significantly shortens the Li + ion diffusion length and facilitates electrolyte mass transportation. The single‐crystalline nature of these LTO microrods is well preserved even after 10 000 cycles.